Developments in the Synthesis and Biological Activity of Glycyl-LHistydyl- L-Lysine Derivatives - Kukowska, M.; Dzierzbicka, K. (Current Medicinal Chemistry, 2014)
Three decades of extensive research on biological activity of natural tripeptide Gly-His-Lys has established the substructure for development of its novel derivatives which give hope for widening the application in the field of medicine and dermatology. Synthetic approaches to obtain Gly-His-Lys and its modifications provide both classical solution method and solid phase peptide synthesis, usage of different protecting groups and methods of peptide bond formation. In our present review, we emphasize on the methods of the synthesis described in the literature and present the aspects of Gly-His-Lys structure modifications that played a key role in scientific research.
Keywords: hydrophobic derivatives